2011
DOI: 10.1186/1471-2334-11-349
|View full text |Cite
|
Sign up to set email alerts
|

Latent tuberculosis infection, tuberculin skin test and vitamin D status in contacts of tuberculosis patients: a cross-sectional and case-control study

Abstract: BackgroundDeficient serum vitamin D levels have been associated with incidence of tuberculosis (TB), and latent tuberculosis infection (LTBI). However, to our knowledge, no studies on vitamin D status and tuberculin skin test (TST) conversion have been published to date. The aim of this study was to estimate the associations of serum 25-hydroxyvitamin D3 (25[OH]D) status with LTBI prevalence and TST conversion in contacts of active TB in Castellon (Spain).MethodsThe study was designed in two phases: cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 49 publications
2
34
0
3
Order By: Relevance
“…Scientific research is studying the effect of vitamin D on the course of the TB disease. A recent study in Spain indicated that a high proportions of contacts of TB patients had low serum 25(OH)D levels and suggested that sufficient 25(OH)D levels protect against tuberculin skin test (TST) conversion, therefore supporting the hypothesis that deficient vitamin D status is a TB risk factor [44].…”
Section: Vitamin D Deficiency and Tbmentioning
confidence: 89%
“…Scientific research is studying the effect of vitamin D on the course of the TB disease. A recent study in Spain indicated that a high proportions of contacts of TB patients had low serum 25(OH)D levels and suggested that sufficient 25(OH)D levels protect against tuberculin skin test (TST) conversion, therefore supporting the hypothesis that deficient vitamin D status is a TB risk factor [44].…”
Section: Vitamin D Deficiency and Tbmentioning
confidence: 89%
“…These include a clinical trial in Mongolian children on TBIC (14), a study of TB disease in Pakistan (4), and another study in Africa with HIV patients (15). In these studies, low VitD levels were associated with an increase of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all participants were interviewed about TB risk factors. A more detailed methodology has been reported in previous publications (15,16). For the participants, chemoprophylaxis against TB was recommended, taking into account exposure, age, clinical conditions, and the characteristics of the index TB case.…”
Section: Tuberculosis Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…25hydroxyvitamin D levels lower than 80 nm in liter is generally believed to be deficient. Another new and different action which recently ascribed forvitamin D is its anti-proliferative and (14).…”
Section: Discussionmentioning
confidence: 99%